2008
DOI: 10.1002/cbic.200700457
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Characterization of Fusogenic Domains in Herpes Virus Glycoprotein B Molecules

Abstract: The molecular mechanism of entry of herpes viruses requires a multicomponent fusion system. Virus entry and cell-cell fusion of Herpes simplex virus (HSV) requires four glycoproteins: gD, gB and gH/gL. The role of gB remained elusive until recently, when the crystal structure of HSV-1 gB became available. Glycoprotein B homologues represent the most highly conserved group of herpes virus glycoproteins; however, despite the high degree of sequence and structural conservation, differences in post-translational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 47 publications
(51 reference statements)
4
67
0
Order By: Relevance
“…Moreover, recent data have shown that peptides spanning the heptad-repeat region of gH inhibit the entry of both human cytomegalovirus (31) and HSV-1 (29,30), similar to the corresponding entry inhibitors identified for viruses that have a class I membrane-fusion protein.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Moreover, recent data have shown that peptides spanning the heptad-repeat region of gH inhibit the entry of both human cytomegalovirus (31) and HSV-1 (29,30), similar to the corresponding entry inhibitors identified for viruses that have a class I membrane-fusion protein.…”
mentioning
confidence: 56%
“…gH has been reported to have certain features that are characteristic of class I fusion proteins, such as the presence of heptad repeats and a putative fusion peptide region (21,29,30). Moreover, recent data have shown that peptides spanning the heptad-repeat region of gH inhibit the entry of both human cytomegalovirus (31) and HSV-1 (29,30), similar to the corresponding entry inhibitors identified for viruses that have a class I membrane-fusion protein.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, gH carries elements typical of fusion glycoproteins, i.e. hydrophobic regions able to interact with target cells or artificial membranes and two heptad repeats potentially able to form a coiled coil (13)(14)(15)(16)(17)(18). Peptides mimicking the hydrophobic regions of gH promote fusion of artificial membranes (19,20).…”
Section: Herpes Simplex Virus (Hsv)mentioning
confidence: 99%
“…10,11 The intrinsic ability of virus-derived peptides to induce membrane perturbation may be useful in the design of delivery vehicles. [12][13][14] The peptide gH625, previously identified as a membraneperturbing domain in glycoprotein H (gH) of herpes simplex virus 1, has been demonstrated to be able to traverse the membrane bilayer. 15 Further, gH625 has been used extensively for vector-mediated strategies that enable passage of a large variety of small molecules as well as proteins across cell membranes in vitro.…”
mentioning
confidence: 99%